2014
DOI: 10.1140/epjp/i2014-14005-7
|View full text |Cite
|
Sign up to set email alerts
|

Average clock times for scattering through asymmetric barriers

Abstract: The reflection and transmission Salecker-Wigner-Peres clock times averaged over the postselected reflected and transmitted sub-ensembles, respectively, are investigated for the one dimensional scattering of a localized wave packet through an asymmetric barrier. The dwell time averaged over the same post-selected sub-ensembles is also considered. The emergence of negative average reflection times is examined and we show that while the average over the reflected sub-ensemble eliminates the negative peaks at reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…A similar definition of the distribution of tunneling times given in ( 10)-( 11) can be obtained for any time scale which is probabilistic in nature, that is, of the form (8). Although several other probabilistic tunneling times exist in the literature (e.g., [23,31,32,35]), the SWP clock has proven to yield well-behaved real times both in the time-independent [17,37,39] and time-dependent approaches [28,34,40] and it provides a simple procedure to derive the probabilistic expression (8). In addition, the role exerted by circularly polarized light in attoclock experiments [3,25] seems to provide a natural possibility for interpretation in terms of the SWP clock.…”
Section: The Tunneling Times Distributionmentioning
confidence: 89%
See 1 more Smart Citation
“…A similar definition of the distribution of tunneling times given in ( 10)-( 11) can be obtained for any time scale which is probabilistic in nature, that is, of the form (8). Although several other probabilistic tunneling times exist in the literature (e.g., [23,31,32,35]), the SWP clock has proven to yield well-behaved real times both in the time-independent [17,37,39] and time-dependent approaches [28,34,40] and it provides a simple procedure to derive the probabilistic expression (8). In addition, the role exerted by circularly polarized light in attoclock experiments [3,25] seems to provide a natural possibility for interpretation in terms of the SWP clock.…”
Section: The Tunneling Times Distributionmentioning
confidence: 89%
“…A few works (e.g., [23,28,31,32]) address the issue of localizability and, consequently, arrive at a probabilistic definition of tunneling times (that is, an average time). In particular, in [28] the SWP clock was used to obtain an average tunneling time of transmission (reflection) for an incident wave packet, and such time was employed to investigate the Hartman effect [33] for a particle scattered off a square barrier and it was shown that it does not saturates in the opaque regime [28,34].…”
Section: Introductionmentioning
confidence: 99%
“…where we have defined the auxiliary phase ϕ 0 (k, q), which allow us to introduce the auxiliary clock and phase times [62,63] given, respectively, by…”
Section: Odd Arrangementsmentioning
confidence: 99%
“…With the help of these auxiliary times, the transmission and reflection times are now related by It should be noticed that, contrary to the case of even potentials, for odd potentials (and potentials without a defined parity) the clock times in general do not coincide with the dwell time [63]. Below we consider two cases of odd arrangements of point interactions, the first built from two δ and the second built from two δ ′ interactions.…”
Section: Odd Arrangementsmentioning
confidence: 99%